Dramaturgia do aqui e agora: presença, recepção e sentido no corpo do ator - Toledo, Marina Madeira de (2013)
The actor is an actor during all the phases of creation and development of his character. (S) He goes beyond the moment of interpreting. In this sense, in her (his) daily life, the actor may use her (his) potential to extract from reality the necessary elements for the work of creation. This is a theoretical research which focus on the concept of presence in the actor s work, stretching the concept beyond the scene, encompassing different components such as the body, the word, the silence, the technique and the acting as the actor s stance in regards to his own reality. The objective of such stance is to integrate him (her) self in the environment, balancing his (hers) inner life with the outside life flow. To reach this objective, the research drew theoretical resources from the concept of presence in the actor s work according to BROOK, BARBA, GROTOWSKI and MNOUCHKINE and the studies on reception theory in ISER, 1996; GUMBRECHT, 2010. Thus, the dialogue between reader and actor high lights both as receivers in this work. A practical description of a street theater Kamchàtka show, featured by the Kamchàtka Company is used as an example of the research on the presence. The elements localized in this show are: play, listening, word, silence, meaning, relationship with here and now and the effects of the said presence